Analyzing the Impact of Entrepreneurial Orientation on Sustainable Business Performance using Hierarchical Linear Regression - Amaleshwari, Umapathy; Jeevitha, Ramamoorthy (INTI International University, 2024)
This research explores the relationship between Entrepreneurial Orientation (EO) and Sustainable business performance (SBP). EO is a strategic posture characterized by innovativeness, proactiveness, risk-taking, autonomy and competitiveness which are hypothesized to influence SBP positively. The study aims to explore how these EO dimensions contribute to achieving sustainable outcomes across various industries. Data for the analysis is collected from a diverse sector which includes manufacturing and service focusing on their strategic orientations and their sustainability policies. Data was collected from the senior and mid level managers of 150 small and medium scale companies in Chennai. Proposed hypotheses were tested using hierarchical linear regression analysis. Understanding the impact of EO along with Technology capabilities on SBP can provide insights into how firms can effectively leverage entrepreneurial behaviors to enhance their sustainability performance. For practitioners, the research highlights specific areas— such as fostering innovation, proactive environmental management, and calculated risk-taking— that can lead to improved sustainability outcomes.